Percepções de professoras de escolade públicas eucação infantil acerca de sua formação e prática educativa: o caso de Medianeira - PR - De Marco, Marilete Terezinha [UNESP] (2015)
This work aims to share the performed studies in a Master´s degree research at the Pos Graduation Program in Education of Unesp, Campus Marilia, São Paulo. As the main objective of these studies, it was delimited to check the perceptions of the Infant Education teachers about the (des) compasses between their initial and continuous formation and their practice effectively performed. Our investigation problem was: what are the perceptions of the Infant Education public school teachers of Medianeira, Paraná, about their initial and continuous formation? The theoretical fundamentals used during the literature review focused, especially at the studies on the Historical-Cultural Theory. We also bring other contemporary authors to highlight the teacher´s training value with the child´s work and the impacts of the learning arising from this formation for their pedagogical practices. As a tool of data production, we use the semi-structured interview with eight child´s teachers and the observation of two pedagogical situation of each one of them. By the researched teachers´ reports and the observed pedagogical situations during the investigation, we understand that the teacher´s training courses still do not attend the contents considered essentials for the good teacher´s practice. We defend that the teacher´s training focused to the Infant Education must privilege knowledge from different areas that are capable to guide pedagogical actions focused to the full child´s development, searching for the effectiveness of their multiple possibilities and the learning capacity. In this perspective, the Infant Education teacher´s training process covers the constitution of essential knowledge to a humanizing education, that during childhood means to educate caring and to care educating, recognizing the individual needs and respecting the child social, historical and cultural differences